Transcendent and Aesthetic Experience of Religious Art in Eastern Orthodox Christianity: Iconography, Ritual, and Psychology - Dimitrijević, Aleksandra R.; Todić Jakšić, Tijana R.; Stojilović, Ivan Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Religious art, particularly Eastern Orthodox Christian iconography and liturgical practice, plays a crucial role in shaping the spiritual and aesthetic experience of believers. This paper examines how religious art is perceived on a subjective level, analysing the interplay of aesthetic, cognitive, emotional, and transcendent elements. Grounded in the Orthodox tradition, the study explores a model of Orthodox aesthetics encompassing divine, worldly, human, and artistic beauty, before introducing the concept of the transaesthetic experience (Ott, 2013). Through the lens of psychology of art, aesthetic experience, and religious rituals, the study investigates the mechanisms by which Orthodox art serves as a mediator between the material and the spiritual. By analysing Orthodox iconography, liturgical gestures, and worship experiences, this paper also proposes an extended model of subjective experience in religious art. This model comprises six key dimensions: emotional, visual-aesthetic, cognitive, communicative, spiritual-transformative, and sociocultural. Preliminary research suggests that believers experience religious art through a multi-layered relationship with faith, culture, and personal identity, whereas for non-religious observers, the aesthetic dimension remains primary. This study contributes to a deeper understanding of religious art not only as an aesthetic phenomenon but also as a medium for profound spiritual and psychological introspection.